2002
DOI: 10.1111/j.1469-8749.2002.tb00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathological long‐bone fractures in residents with cerebral palsy in a long‐term care facility in South Africa

Abstract: A high incidence of long‐bone fractures has been observed in children and young adults with quadriplegic cerebral palsy in residential care. This study aimed to determine factors that contribute to these fractures and to institute preventive treatment. Twenty individuals (12 males, eight females) of a cohort of 88 residents with spastic quadriplegia in residential care in Gauteng, South Africa who had sustained fractures were compared with a random sample of age‐matched control participants (10 males, 10 femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 15 publications
(14 reference statements)
0
19
0
Order By: Relevance
“…A study showed that all 20 institutionalized children and young adults with quadriplegic CP and a history of long-bone fractures had radiological and biochemical evidence of rickets or osteomalacia, and vitamin D treatment resulted in marked clinical improvement with no recurrence of fracture during the treatment period. 5 Growth hormone may also be deficient in children with CP. A recent large-scale study of 46 children with CP aged between 3 and 11 years showed that 70% of these children lacked normal growth hormone secretion.…”
Section: Prevention Of Bone Fragility and Fractures In Children With mentioning
confidence: 97%
See 4 more Smart Citations
“…A study showed that all 20 institutionalized children and young adults with quadriplegic CP and a history of long-bone fractures had radiological and biochemical evidence of rickets or osteomalacia, and vitamin D treatment resulted in marked clinical improvement with no recurrence of fracture during the treatment period. 5 Growth hormone may also be deficient in children with CP. A recent large-scale study of 46 children with CP aged between 3 and 11 years showed that 70% of these children lacked normal growth hormone secretion.…”
Section: Prevention Of Bone Fragility and Fractures In Children With mentioning
confidence: 97%
“…17 Furthermore, a significant relationship between the number of pathological long bone fractures and the use of AEDs was demonstrated in institutionalized residents with CP. 5 In summary, severe neurological impairment (non-ambulatory status, GMFCS level V), severe joint contracture, a history of fracture, prolonged immobilization (particularly the use of a hip spica), malnutrition (Ryles tube feeding or gastrostomy, low body weight z-score) and use of AEDs are known to be associated with an increased fracture risk in children with CP.…”
Section: Risk Factors Associated With Fractures In Children With Cerementioning
confidence: 99%
See 3 more Smart Citations